MENINGKATKAN KOMPETENSI GURU DALAM PENGELOLAAN KELAS BERBASIS EKOLOGI DI SD AL-IHSAN - Yufiarti; Ratna Dyah Suryaratri (Bahasa Indonesia, 2020)
Abstract The purpose of community service is to improve teacher competence in managing classes in ecology-based target schools. Various student problems can occur because the teacher is less skilled in managing the class. The first problem is that the teacher does not understand the characteristics of children and how to solve problems so that the class becomes ineffective. The service was carried out for 6 meetings involving teachers around the Insan Elementary School. The training method starts with problem identification using the interview method with both the teacher and the principal. The training is carried out by the head of the foundation and the principal as well as teachers and parents of students. Based on the results of the teacher training evaluation instrument, it can increase knowledge about the characteristics of children and how to approach various children according to their learning mode. The teacher can identify the child's learning modality. Implementing community service activities to increase teacher competence in managing ecological-based classrooms can be carried out properly. Abstrak Tujuan pengabdian masyarakat adalah untuk meningkatkan kompetensi guru dalam mengelola kelas di sekolah sasar berbasis ekologi. Berbagai permasalah siswa dapat terjadi karena guru kurang terampil mengelola kelas. Permasalahan pertama adalah guru kurang memahami karakteristika anak dan cara mengatasi permasalahan sehingga kelas menjadi tidak efektif. Pengabdian dilakukan selama 6 kali pertemuan dengan melibatkan guru disekitar Sekolah Dasar Insan. Metode pelatihan dimulai dari identifikasi permasalahan menggunakan metode wawancara baik dengan guru maupun kepala sekolah. Pelaksanaan pelatihan terdiri oleh ketua Yayasan dan Kepala Sekolah serta guru dan orang tua siswa. Berdasarkan hasil instrument evaluasi pelatihan guru dapat meningkatkan pengetahuan tentang karakteristik anak dan bagaimana cara mendekati beragam anak sesuai dengana modality belajr mereka. Guru dapat mengidentifikasi modality belajar anak. Pelaksanaak kegiatan pengabdian peningkatan kompetensi guru dalam mengelolan kelas berbasis ekologis dapat dilaksanakan dengan baik.